Understanding the Concept of Language of Mathematics for Effective Teaching and Learning of Mathematics in a School System - Joseph, Joseph Ugochukwu (International Journal for Educational and Vocational Studies, 2020)
The paper deals with understanding the concept of language of mathematics for effective teaching and learning of mathematics in a School System. It as well looked at the causes of students’ failure in mathematics in internal and external examinations to include lack of understanding of mathematics language. The persistent poor performance of students in internal and external examinations in mathematics has become an issue of concern to Mathematics educators, and relevant stakeholders.  Findings of recent research studies in mathematics education have identified inadequate understanding of mathematics language to translate word problems into mathematical form as one of the factors responsible for poor performance. Hence, this paper examined the language of mathematics and its understanding. Specifically, the paper discussed the algebraic language; the language of basic operations; the language of set theory; the language of functions; the language of relations; the logical language and the language of differential calculus. The paper further examined the usefulness of variables; difficulties in learning mathematical language and made some recommendations among many others to include that mathematics teachers should teach the mathematical language instruction in mathematics before proceeding to the topic proper to enhance better performances of students in mathematics.